2018
DOI: 10.1111/nmo.13304
|View full text |Cite
|
Sign up to set email alerts
|

Micro‐inflammation in functional dyspepsia: A systematic review and meta‐analysis

Abstract: Functional dyspepsia (FD) is a gastrointestinal disorder of unknown etiology. Although micro-inflammation appears to be important in the pathogenesis, studies evaluating immune activation in FD have been inconsistent. A systematic review of literature and meta-analysis was performed to compare immunologic cell counts and cytokine levels in the mucosa and peripheral blood of individuals with FD and healthy controls. PubMed, Embase, and the Cochrane library were searched. Data on immunologic cell counts and cyto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
58
0
12

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(74 citation statements)
references
References 49 publications
4
58
0
12
Order By: Relevance
“…It is also possible that chronic cholecystitis and biliary dyskinesia are two distinct conditions without overlap and that the differentiation can only be made definitively after cholecystectomy. Additionally, or alternatively, biliary dyskinesia might be associated with mucosal mast cells, also analogous to what has been reported with functional dyspepsia and irritable bowel syndrome (50,51). Compared to autopsy controls, we have previously demonstrated a >9fold increase in gallbladder mast cell density in children with biliary dyskinesia (52).…”
Section: Histopathologysupporting
confidence: 83%
“…It is also possible that chronic cholecystitis and biliary dyskinesia are two distinct conditions without overlap and that the differentiation can only be made definitively after cholecystectomy. Additionally, or alternatively, biliary dyskinesia might be associated with mucosal mast cells, also analogous to what has been reported with functional dyspepsia and irritable bowel syndrome (50,51). Compared to autopsy controls, we have previously demonstrated a >9fold increase in gallbladder mast cell density in children with biliary dyskinesia (52).…”
Section: Histopathologysupporting
confidence: 83%
“…Since the description by Toukan et al 24 of infiltration of the duodenum by eosinophils in patients with FD, several studies have demonstrated significant infiltration of eosinophils into the upper GI tract in patients with FD. 16,[26][27][28][29] In a Swedish population-based study, the degree of infiltration of eosinophils and mast cells into the duodenum was sampled randomly in 51 patients with FD and 41 patients with IBS. The results suggested that the number of eosinophils, but not mast cells, is increased significantly in the duodenum of patients with FD, and that the number of mast cells are increased significantly in patients with IBS.…”
Section: Discussionmentioning
confidence: 99%
“…In another cohort, the duodenal eosinophilia was related with early satiety/fullness, not epigastric pain, 27,34 however, other recent studies showed no significant differences between EPS and PDS. 29,35 In the latter, a significant amount of eosinophils and mast cells infiltrated the submucosal layer combined with altered submucosal ganglionic architecture and accompanied by decreased calcium responses to depolarization in FD. 35 The contribution of the submucosal nerve plexus to normal gastric motility is probably minimal because gastric submucosa contains few intrinsic primary afferent neurons and the intrinsic reflexes are poorly developed.…”
Section: Discussionmentioning
confidence: 99%
“…Подтверждением этому являются исследования, в которых сообщается об увеличении количества тучных клеток и эозинофилов в биоптатах слизистой оболочки двенадцатиперстной кишки, что подчеркивает потенциальную роль воспалительных механизмов в патогенезе ФД [29]. Так, в недавнем метаанализе, обобщившем результаты 37 исследований, было продемонстрировано, что у пациентов с ФД по сравнению с группой контроля отмечается увеличение количества тучных клеток (стандартизованная разность средних (СРС) = 0,66, 95% ДИ 0,20-1,13, p = 0,005) и эозинофилов (СРС = 0,95, 95% ДИ 0,66-1,24; p < 0,001) в слизистой оболочке двенадцатиперстной кишки [30]. Данные клетки являются эффекторными и в случае активации вырабатывают большое количество цитокинов, способных оказывать влияние на чувствительность нервных окончаний слизистой оболочки, тем самым индуцируя возникновение феномена ВГ или моторнотонических нарушений гастродуоденальной зоны (описанных выше).…”
Section: этиология и патогенезunclassified
“…С учетом появления все большего количества работ и экспертных мнений касательно роли в генезе ФД субклинического воспаления двенадцатиперстной кишки на фоне нарушения эпителиальной проницаемости на сегодняшний день активно изучаются терапевтические возможности назначения лекарственных средств, обладающих цитопротективным действием по отношению к слизистой оболочке ЖКТ [12,28,49]. В настоящий момент доказательная база эффективности гастропротективных препаратов при ФД продолжает активно формироваться.…”
Section: лечениеunclassified